2018
DOI: 10.1177/0961203318791046
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in juvenile onset lupus: single center cohort from a developing country

Abstract: Introduction About 10-20% of systemic lupus erythematosus (SLE) patients have onset in childhood and have more severe organ involvement. Survival of juvenile SLE patients is improving worldwide. Long-term data of childhood onset SLE from developing countries is scarce. Methods Clinical and laboratory data at initial presentation and follow-up visits were retrieved from clinic files, hospital information system and personal interviews. Treatment received, complications, flares, outcomes and death were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…Our finding that 39% of youth who died had infectious diseases as their primary diagnosis demonstrates once again that infection is a major complication of the rheumatic diseases. The rate of infection we found was higher than reported by Butt et al in a Danish cohort with systemic sclerosis [37] and by Aggarwal et al in an Indian cohort of youth with lupus [38] but similar to the Chinese lupus cohort of all ages by Mu et al [39] We also found that patients with vasculitis and scleroderma were at higher risk of dying in the hospital relative to patients with other rheumatic diseases (of which lupus was the most frequent comparator diagnosis). While this can be explained by the increased severity of these diseases, they are understudied in the transition literature [40,41].…”
Section: Discussionsupporting
confidence: 74%
“…Our finding that 39% of youth who died had infectious diseases as their primary diagnosis demonstrates once again that infection is a major complication of the rheumatic diseases. The rate of infection we found was higher than reported by Butt et al in a Danish cohort with systemic sclerosis [37] and by Aggarwal et al in an Indian cohort of youth with lupus [38] but similar to the Chinese lupus cohort of all ages by Mu et al [39] We also found that patients with vasculitis and scleroderma were at higher risk of dying in the hospital relative to patients with other rheumatic diseases (of which lupus was the most frequent comparator diagnosis). While this can be explained by the increased severity of these diseases, they are understudied in the transition literature [40,41].…”
Section: Discussionsupporting
confidence: 74%
“…There is also a markedly increased risk of cardiovascular disease in adulthood [ 84 , 85 ]. Ten-year survival for JSLE in LRIC and MRIC is approximately 80% [ 2 , 80 , [86] , [87] , [88] , [89] , [90] ] compared with 99% in HRIC [ 85 ], with lupus nephritis and infection, the major causes of death [ 91 , 92 ].…”
Section: Impact Described Through Selected Msk Conditionsmentioning
confidence: 99%
“…Diagnosis can be challenging where infections (such as TB) are often mimics of rheumatic diseases and diagnostic capabilities (including availability of autoantibody tests) are often limited in low resource settings [ 5 , 95 ]. Delayed diagnosis and access to specialist care in JSLE with worse clinical outcomes is widely reported across the world [ 79 , 88 , [96] , [97] , [98] ], often associated with more severe disease activity and organ damage at presentation [ 75 , 99 , 100 ]. Many of the innovations that have improved survival in HRIC remain unavailable in most of the world [ 77 ] and access to renal replacement therapy may be severely limited or non-existent [ 101 ].…”
Section: Impact Described Through Selected Msk Conditionsmentioning
confidence: 99%
“…Advancements of immunosuppressive therapy in systemic lupus erythematosus (SLE) improve patient survival. 1 However, the use of potent immunosuppressive medications is associated with increased rates of infection-related morbidity and mortality. 2 Infection contributes to 30% of deaths in the first 5 years of disease and infection increases standardized mortality ratio in patients with SLE five-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Children account for 10–20% of patients with SLE and 50–70% of them develop lupus nephritis (LN) with class IV the most common. 1 Infection is the leading cause of death in childhood-onset SLE as children often require intense immunosuppression to control the disease. 4 A recent study has shown that severe sepsis is the only independent risk factor of death in childhood-onset SLE and associated with nearly a 100-fold increase in the risk of death.…”
Section: Introductionmentioning
confidence: 99%